why is it that you can substitute x=3. I know you got that from the divisible by x-3 and carried over the 3, but how did you know to do that?
if 2x^2-3x-m is divisible by x-3, it means that x-3 multiplies with something will be equal to sx^2-3x-m
when you solve ax^2+bx+c question, you normally equate it with 0 and find value of x by finding factors
so in this case, i go with this
2x^2-3x-m = (x-3) * A = 0
this means than x=3 must be one of the solutions of equation
so i choose o substitute that and find m =9